pls solve this as soon as possible....it's urgent
Attachments:
![](https://hi-static.z-dn.net/files/df2/7e1f83aabbd862f31c632d664b6fb3a2.jpg)
Answers
Answered by
1
Heya
_______________________________
L.H.S
( 1 - Cos x )²
_______
( Sin x )²
=>
( 1 - Cos x ) × ( 1 - Cos x )
__________________
( 1 - Cos x ) × ( 1 + Cos x )
=>
( 1 - Cos x )
________
( 1 + Cos x )
Hence proved
______________________________
Sin² x = 1 - Cos² x
And
( 1 - Cos x )². = ( 1 - Cos ) × ( 1 - Cos )
_______________________________
L.H.S
( 1 - Cos x )²
_______
( Sin x )²
=>
( 1 - Cos x ) × ( 1 - Cos x )
__________________
( 1 - Cos x ) × ( 1 + Cos x )
=>
( 1 - Cos x )
________
( 1 + Cos x )
Hence proved
______________________________
Sin² x = 1 - Cos² x
And
( 1 - Cos x )². = ( 1 - Cos ) × ( 1 - Cos )
hibha66:
Thanks bro... it was really helpful to me
Similar questions